Annual report for year, 1942-3
1943-04-02 038-0016-006 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF COMBINED RECEIPTS AND PAYMENTS ACCOUNT (HEAD OFFICE) FOR THE YEAR ENDED 31st DECEMBER, 1942. Receipts £ s. d. £ s. d Cash in hand and at bank - 1st January, 1942 954 6 6 £944 8s. 4d. 3½% War stock at cost 997 10 9 1,951 17 3 Donations, subscriptions and proceeds of appeals 4,180 7 7 Sale of office furniture 20 0 0 Interest on £944 8s. 4d. 3½% War Stock 33 1 0 Loan 75 0 0 £ 6,260 5 10 Payments £ s. d. £ s. d. Basque Children's Account Contributions towards Maintenance and Equipment of Homes 1,415 11 8 Basque Boys' Training Account Contributions towards Maintenance 459 6 0 British Committee for Refugees from Spain Account Expenditure on Maintenance (United Kingdom) 69 5 0 1,944 2 8 Travelling Expenses 170 10 4 Total Relief Expenditure for the Year to Date 2,114 13 0 ADMINISTRATIVE EXPENSES Salaries and Wages 706 5 9 Rent, Rates, Cleaning, Lighting, Heating and Telephone 183 13 5 Postage, Printing and Stationery 500 3 6 Annual Report 69 0 6 Travelling Expenses 37 6 4 General Expenses 38 11 11 1,535 1 5 Cash in Hand and at Bank - 31st December, 1942 1,613 0 8 £944 8s. 4d. 3½% War Stock at Cost 997 10 9 2,610 11 5 £6,260 5 10 Prepared from the books vouchers and records of the Committee and certified to be in accordance therewith and correct according to our information. Included in the closing balance of Cash in Hand and at Bank is an amount of £64 1s. 7d. which was held in Paris at 31st December, 1939, and in respect of which no information later than that date is at present available. We have verified the holding of £944 8s. 4d. 3½% War Stock. JOHN DIAMOND & Co., Chartered Accountants, 73, Basinghall Street, E.C.2. London: 2nd April, 1943. 292/946/38/16(VI)